If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5g + 6 = 51 Reorder the terms: 6 + 5g = 51 Solving 6 + 5g = 51 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 5g = 51 + -6 Combine like terms: 6 + -6 = 0 0 + 5g = 51 + -6 5g = 51 + -6 Combine like terms: 51 + -6 = 45 5g = 45 Divide each side by '5'. g = 9 Simplifying g = 9
| 41=-4-(5x) | | 12+c=24 | | 10x+14x=10-4 | | m-18=36 | | 4(3x-2)+2(3x+3)=3x+28 | | 5a+10b-4a-7b= | | x^4*x^7= | | k=14 | | -(1x+4)=-3x | | 4(a-15)=64 | | 14n+12p+4n+12p= | | 3x-y(5-x)=7 | | p-15=48 | | -2(4)-3(-5)= | | 5k+14m+4k+12m= | | 25(x-y)= | | 4-10.00+x=44 | | 7r+20=41 | | 5*3x=12 | | 2x^2+20x+80=0 | | 3w+16=-8 | | -9f-4+8=-32 | | Y=(x-4)(x-2) | | -20+(-2)(-6)= | | r-30=13 | | -9+11x=10x | | 2+(3n+9)=20 | | 9p-13q+12p+19q= | | x+119+x+59=180 | | 15=-3n-3 | | 20+(2)(6)= | | 13f+7g+3f+4g= |